THE EFFECT OF BRAND LOGO ANTHROPOMORPHISM AND BRAND FAMILIARITY ON BRAND TRUST MEDIATED BY BRAND IMAGE (CASE STUDY ON OLIVE FRIED CHICKEN) - Hutdi Nur Cahyono; Singgih Santoso (RADJA PUBLIKA, 2025)
In the increasingly competitive culinary business, building brand trust is a key factor in attracting and retaining customers. Anthropomorphism of brand logos and brand familiarity can play an important role in forming a positive brand image, thus influencing the level of consumer trust. This study aims to analyze how these two factors contribute to brand trust in Olive Fried Chicken, considering the mediating role of brand image. This study uses a non-experimental quantitative approach with a focus on Olive Fried Chicken consumers in the Special Region of Yogyakarta and its surroundings. Data were collected through a questionnaire with a Likert scale, using a purposive random sampling method with a sample of 350 respondents. Data analysis was carried out using descriptive statistics and Structural Equation Modeling (SEM) using AMOS 24 to test the causal relationship between variables and confirm the validity and reliability of the instrument through Confirmatory Factor Analysis (CFA). This study shows that logo anthropomorphism and brand familiarity have a positive and significant influence on brand image, which in turn has an impact on increasing brand trust. Brand image acts as a mediator in the relationship between logo anthropomorphism and brand familiarity with brand trust, confirming that a strong image can strengthen consumer trust. Therefore, companies are advised to optimize branding strategies through more anthropomorphic logo designs and increased brand familiarity to build better brand image and trust.